Analisis Validitas dan Keandalan Tanda Tangan Digital pada Dokumen PDF - Chriscel Novian; Hanif Al Fatta (TIN: Terapan Informatika Nusantara, 2026)
This research aims to analyze the level of validity, measure consistency as a benchmark, and identify the technical metadata factors that influence the validation results of digital signatures. The research scope includes PDF documents with certificates from official authorities or Certificate Authorities (CA) as well as self-signed ones, tested in a Windows 11 environment using Adobe Reader, Foxit Reader, Google Chrome, and Microsoft Edge. An experimental quantitative method was used through a technical approach with automated data processing based on Python scripts for metadata extraction. The research results show a non-uniform level of validation consistency across applications; Foxit Reader achieved the highest accuracy (96.67%), followed by Adobe Reader (91.67%) and Microsoft Edge (90.00%), while Google Chrome (0%) proved to fail completely due to the absence of a cryptographic computation module. The inconsistencies were identified to stem from differences in parser architectures, local security tolerance limits, and software cipher suite library support. Further diagnostic analysis found vulnerabilities due to the absence of third parties such as a Timestamp Authority, as well as an injection security flaw in Microsoft Edge, which failed to detect directory injection attacks. It can be concluded that the absence of standardised PDF parsing can lead to conflicting cross-platform validation results, the reliability of which is entirely dictated by the integrity of the hash algorithm, the cipher suite, the publisher’s status, and the completeness of the timestamp. The contributions of this research include the development of an interoperability benchmark for PDF digital signature validation, the creation of a consistency matrix for cross-platform evaluation, and the identification of technical metadata factors that are the primary determinants of successful validation. The research findings are expected to serve as a reference for application developers, electronic certificate authorities, and organisations in enhancing the security and consistency of digital document validation.